Empirical Characteristics of Dynamic Trading Strategies: The Case of Hedge Funds - Fung, William; Hsieh, David A. (Review of Financial Studies, 1997)
This article presents some new results on an unexplored dataset on hedge fund performance. The results indicate that hedge funds follow strategies that are dramatically different from mutual funds, and support the claim that these strategies are highly dynamic. The article finds five dominant investment styles in hedge funds, which when added to Sharpe's (1992) asset class factor model can provide an integrated framework for style analysis of both buy-and-hold and dynamic trading strategies.